2022
DOI: 10.1002/1878-0261.13212
|View full text |Cite
|
Sign up to set email alerts
|

DRP1 contributes to head and neck cancer progression and induces glycolysis through modulated FOXM1/MMP12 axis

Abstract: Abnormal DRP1 expression has been identified in a variety of human cancers. However, the prognostic potential and mechanistic role of DRP1 in head and neck cancer (HNC) are currently poorly understood. Here, we demonstrated a significant upregulation of DRP1 in HNC tissues, and that DRP1 expression correlates with poor survival of HNC patients. Diminished DRP1 expression suppressed tumor growth and metastasis in both in vitro and in vivo models. DRP1 expression was positively correlated with FOXM1 and MMP12 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…High glucose levels can increase the expression of DRP1, resulting in cell dysfunction and promoting the migration and invasion of endometrial cancer cells ( Guo J. et al, 2020 ). The high expression of DRP1 was correlated with poor survival of head and neck cancer patients ( Huang T. L. et al, 2022 ). DRP1 deletion can affect aerobic glycolysis and suppress tumor growth and metastasis ( Huang T. L. et al, 2022 ).…”
Section: Altered Mitochondrial Dynamics Associated With Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…High glucose levels can increase the expression of DRP1, resulting in cell dysfunction and promoting the migration and invasion of endometrial cancer cells ( Guo J. et al, 2020 ). The high expression of DRP1 was correlated with poor survival of head and neck cancer patients ( Huang T. L. et al, 2022 ). DRP1 deletion can affect aerobic glycolysis and suppress tumor growth and metastasis ( Huang T. L. et al, 2022 ).…”
Section: Altered Mitochondrial Dynamics Associated With Tumorigenesismentioning
confidence: 99%
“…The high expression of DRP1 was correlated with poor survival of head and neck cancer patients ( Huang T. L. et al, 2022 ). DRP1 deletion can affect aerobic glycolysis and suppress tumor growth and metastasis ( Huang T. L. et al, 2022 ). FIS1 is overexpressed in GC, and its expression is correlated with cancer metastasis ( Karimi et al, 2022 ).…”
Section: Altered Mitochondrial Dynamics Associated With Tumorigenesismentioning
confidence: 99%
“…Previous studies have shown that FOXM1 is abundantly expressed in NSCLC and various other cancer (18, 19). Moreover, FOXM1 overexpression was involved in cell cycle, apoptosis and DNA repair regulation, thereby facilitating tumorigenesis and chemoradioresistance through different mechanisms (18,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in mitochondrial dynamics have been also reported in hematological malignancies, as T-cell acute lymphoblastic leukemia and MM [ 15 , 16 ], which enhance the expression and/or activity of fission proteins, like Drp1, to promote survival and resistance to chemotherapy. On this basis, targeting Drp1 holds therapeutic potential in cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%